A review of personality/religiousness associations. (August 2021) - Ashton, Michael C; Lee, Kibeom
Highlights: General religiousness is modestly related to prosocial personality characteristics. Religious fundamentalism and spirituality are related to lower and higher levels, respectively, of the Openness personality dimension. Religiousness/personality associations tend to be stronger in countries whose people are more religious. Abstract : We review research on personality/religiousness associations, integrating earlier meta-analyses with recent large-sample online studies. We find that general religiousness shows small positive associations with broad personality factors (e.g. HEXACO Honesty-Humility, Big Five Agreeableness, Conscientiousness) and somewhat stronger positive associations with narrower personality traits involving prosocial tendencies (e.g. altruism, fairness, forgivingness). The link between religiousness and prosociality appears not to be an artifact of self-report method variance. Religious fundamentalism and spirituality show negative and positive associations, respectively, with the Openness factor of personality. Religiousness/personality associations tend to be weak in relatively non-religious countries but moderately strong in highly religious countries. The direction of causal influence between personality and religiousness is not yet clear. Religiousness shows modest negative associations with IQ and appears to be somewhat negatively related to scientific thinking.